Dependency on planktons of the small indigenous fish species Esomus danricus (Ham) in different habitats - Kahtun, Fatema; Parven, Nousheen; Bashar, MA (Dhaka University Journal of Biological Sciences, 2011)
The food of Esomus danricus (Ham) in experimental conditions (earthen pots and ponds) was studied from June, 2000 to October, 2000. Pond water was supplied in the experimental tanks and ponds to inoculate plankton. Different kinds of organic matters (duck dropping, poultry dropping, rice straw, wheat bran) were used as nutrients for the culture of plankton. Total numerical abundances of phytoplankton production were 5669 and 3905 in the earthen pots and ponds, respectively. The phytoplanktons belonged to Diatomaceae, Myxophyceae, Chlorophyceae, Mesotaeniaceae, Oocystaceae, Desmidiceae and Characiaceae. Total numerical abundances of zooplankton were 3146 and 3785 in earthen pots and ponds, respectively. The zooplankton belonged to Rotifera, Cladocera, Ostracoda and Copepoda. Insect larvae and annelids were also found in considerable numbers. Digestive tracts of the reared fishes were examined. Total numerical abundances of phytoplankton were greater in number (4224) than those of zooplankton (460). It was observed that dependency of Esomus danricus on phytoplankton was greater than zooplankton . Key words: Esomus danricus; Fish production; Plankton; Dependency; Small water reservoirs DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8976 DUJBS 2011; 20(2): 155-161